Stress-induced alterations in resting-state functional connectivity among adolescents with non-suicidal self-injury - Otto, Alexandra; Jarvers, Irina; Kandsperger, Stephanie; Reichl, Corinna; Ando, Ayaka; Koenig, Julian; Kaess, Michael; Brunner, Romuald (Journal of affective disorders, 2023)
BACKGROUND: Non-suicidal self-injury (NSSI) is a major mental health problem among youth worldwide. Dysfunction in emotion regulation contributes to NSSI, but research on the underlying neurobiological mechanisms of NSSI is limited. Adolescents with emotion regulation difficulties are vulnerable to stress, making them susceptible to maladaptive coping mechanisms such as NSSI. METHODS: This study examined the functional neurocircuitry relevant to emotion regulation and stress coping in individuals with NSSI compared with healthy controls. This case-control study included 34 adolescents with NSSI (15.91 years) and 28 (16.0 years) unaffected controls. Participants underwent a functional magnetic resonance imaging scan before and after completing a laboratory stress-induction paradigm (the Montreal Imaging Stress Test). The effects of stress induction were quantified by both physiological measures and self-reports. RESULTS: Participants with NSSI showed distinctive alterations in functional resting-state following stress induction, which differentiated them from unaffected controls. Results show a reduction in functional connectivity between frontoparietal regions and the angular gyrus within the patient group compared to controls, as well as an increase in functional connectivity between visual regions, the insular cortex, the planum polare, and the central opercular cortex. After conditions of acute stress, adolescents with NSSI show changes in functional connectivity of regions associated with sensorimotor alertness, attention, and effortful emotion regulation. LIMITATIONS: The patient group showed both NSSI and suicidal behavior, therefore results might be partly due to suicidality. CONCLUSION: The findings emphasize the importance of targeting emotion regulation within therapeutic approaches to enhance stress coping capacity, which in turn may contribute to counteracting self-injurious behavior.
Online verfügbar: 10 July 2023
Gesehen am 26.10.2023